Dietary carbohydrate quality and risk of breast cancer among women - Bahareh Sasanfar (BMC, 2021)
Abstract Background A few studies have examined the relationship between carbohydrate quality index (CQI) and risk of breast cancer (BC) among women in Middle Eastern countries. We studied the associations between carbohydrate quality index and the risk of BC in overall and by menopausal status. Methods In this case-control study, dietary intake of 461 women with pathologically confirmed BC within the past year were examined. The same information were collected for 495 apparently healthy controls using a 168-item validated FFQ. Carbohydrate quality was determined by considering four criteria including: ratio of solid carbohydrates to total carbohydrates, dietary fiber intake, GI and the ratio of whole grains to total grains. Results Mean GI and GL of participants were totally 57.5 ± 7.2 and 245.7 ± 64.7, respectively. A trend toward significant association was seen between GI and odds of BC in the whole population; such that after stratifying analysis by menopausal status, premenopausal women in the highest quartile of GI were 1.85 times higher likely to have BC than those in the lowest quartile (95% CI: 1.12, 3.07, P = 0.01). We found that women with the greatest CQI had lower odds for BC, compared with those with the lowest CQI (0.63; 95% CI: 0.43–0.94, P = 0.03). This association was remained after stratifying analysis by menopausal status in premenopausal (0.55; 95% CI: 0.34–0.90, P = 0.04). Conclusion We found that GI was directly and CQI inversely associated with odds of BC. In order to determine the effects of dietary carbohydrate quality prospective cohort studies are needed.